RETHINKING THE LEARNING EVALUATION - Odalea M. Brüggemann dos Santos; Elisabeta Roseli Eckert; Maria Emilia de Oliveira; Rosangela Maria Fenili (Universidade Federal de Goias, 2002)
This study sought to know and understand how Nursing Graduation Course at Santa CatarinaFederal University evaluates the students. It analyses how the evaluation is structured in teaching programs ofeight subjects of professional period. From data analyses it is possible to observe that the subjects use as a criteriathe marks and all of them attribute different levels to each activity, according to established criteria of the teachers.Thus, it can be said that what is done as learning evaluation is merely a verification. In this sense, the authorspoint out some ways that can redirect this practice.